Observational study of body weight, body fat with segmental fat distribution, visceral fat and body mass index in type 2 diabetic patients - Dube, Sunil; Viswanathan, Shanti; Dube, Manjree (International Journal of Research in Medical Sciences, 2016)
Background: There has been an increase in the prevalence of non-communicable diseases in the last decade. This prevalence has been steadily increasing and is expected to increase further in the coming decade. The change in our lifestyle plus a sedentary lifestyle has led to this .Various body composition monitoring methods help us evaluate obesity and its association with diabetes. In this study, we analysed the trend of body fat distribution in diabetics. Methods: A multifrequency body composition monitor TANITA MC 980 was used to analyse visceral fat, body fat and segmental fat distribution. This was correlated with BMI. Results: BMI showed a significant correlation between body fat (R2=0.558) and visceral fat (R2=0.166) where R>0.5 is significant. BMI showed a negative correlation with upper and lower body adiposity. Linear regression analysis also showed a positive relation between BMI and visceral fat and BMI and body fat. The overall accuracy of body fat and visceral fat to assess obesity was 0.829 and 0.731 respectively. Conclusions: This study showed a positive correlation between BMI and visceral fat as well as body fat as measured by bioelectric impedance method. Visceral fat being a definite risk factor for development of Type 2 diabetes and its association with other comorbidities, there is a need not only to measure body fat but also visceral fat in type 2 diabetes.